Profile of children's hospitalizations for cleft lip and/or palate in Northeast Brazil (Research, Society and Development, 2021)
Cleft lip and/or palate are the most common congenital malformations of the head and neck, and occur due to the lack of fusion of embryonic facial processes, during the period between the fourth and seventh weeks of intrauterine life. This study aims to analyze the profile of children hospitalized with cleft lip and/or palate in the Northeast region of Brazil, in the period from 2015 to 2019. This is an observational and transversal, retrospective, descriptive, qualitative epidemiological study with documentary approach, in which the cases were analyzed regarding the following parameters: age, gender, color, character of service and distribution by state. The data were collected in the SUS Hospital Information System (SIH / SUS) through DATASUS, released in Excel and submitted to statistical analysis in IBM SPSS Statistics for Windows. 6598 hospitalizations for cleft lip and / or palate were recorded in the period from 2015 to 2019. It was observed that the attendance of an elective character was prevalent to the emergency, with Bahia being the state with the highest number of hospitalizations when taking into account both characters. As for age, gender and ethical-racial group, it was found that brown children, aged 1 to 4 years and male were the most affected. In addition, 10 deaths occurred during the study period. It is hoped that this study will bring information to the reader and point to the importance of continuing research on the topic, offering a greater diffusion about the medical situation of these patients.